SOSIALISME BUNG KARNO: MEMAHAMI IMAJINASI SOSIAL BUNG KARNO - Rudiyanto Rudiyanto (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2017)
This paper attempts to look at the ideas of Sukarno in regulating the nation with the theory of Social Imaginary. This theory speaks about portrayal of a nation through the eyes of the people. The portrayal is usually projected through legends, tales folktales and so forth. This paper saw Sukarno combines Western Social Imaginary with Social Imaginary of Indonesia to build a society of Indonesia. Sukarno then combines the concept of Internationalism to Nationalism. As well as the people’s democracy or Marhaen with a conviction if people politically sovereign and economically the nation will experience social justice.